Space based inputs for health service development planning in rural areas using GIS - Kuldeep, _; Banu, Vijaya; Uniyal, Swati; Nagaraja, R. (Geodesy and Cartography, 2017)
The use of Geospatial Techniques for quick decision making is the demand of the time. Geospatial techniques play a very important role to help decision makers, stakeholders and citizens for planning at various levels of governance. Geospatial technology is fast and accurate enough to make analysis and derive the useful results to help the decision makers in planning process. This has augmented the need for development of a model utilising the geospatial datasets to automatize the process which can aid in quick decision making for effective planning and development at village level. The objective of this research work is to build a spatial model for identifying suitable sites for hospital in rural areas. A pilot study has been carried out which aims to identify and prioritize the potential sites for hospitals/Clinic utilizing the 1:10 k scale database with the help of Geographic Information System (GIS) in Hisar, Harayana, India. This study identifies the following factors as indicators of suitability for landscape: road connectivity, demography and location of existing facilities. The evaluating process for suitable hospital/clinic sites have been carried out based on five chosen criteria including land use/cover type, road network and settlement location, proximity to existing facilities and population. The outcome of the model has been further used as input to Location-allocation tool in GIS to select the suitable location for medical and health facilities. The adopted methodology identifies the 10 new suitable sites for medical and health facilities by putting all the criteria with the actual resources of the region. The proposed approach can be effectively utilized by the Government for Health Service Development Planning in Rural areas where medical and health facilities are poor.